Procesado masivo y automático de trazas en redes celulares - Anaya-López, G. J.; Guerra-Melgares, Noelia; Cárdenas-Angelat, Carlos; Aguayo-Torres, María del Carmen; Baños-Polglase, Juana Daphne (My University, 2019)
The introduction of new services in mobile communications usually requires extensive evaluation campaigns. Even though new services and devices may have undergone conformance testing, it is important to ensure they do properly work in real live networks, where some parameters, signalling procedures or timer values may differ from those used in conformance testing. It is also important to diagnose error sources. This paper describes a tool that automatically analyses traces captured by the mobile terminal. Its design addresses two main challenges: the efficient handling of the large amount of information captured by the terminal and the extraction of relevant information from traces generated by different sources.
Keywords: Teléfonos móviles; Comunicaciones; Red celular; Trazas